Ultrafast Excited-State Decays in [Re(CO) 3 (N,N)(L)] n+ : Nonadiabatic Quantum Dynamics - Fumanal, Maria; Gindensperger, Etienne; Daniel, Chantal (Journal of chemical theory and computation, 2017)
The ultrafast luminescent decay of [Re(CO) (phen)(im)] , representative of Re(I) carbonyl α-diimine photosensitizers, is investigated by means of wavepacket propagations based on the multiconfiguration time-dependent Hartree (MCTDH) method. On the basis of electronic structure data obtained at the time-dependent density functional theory (TD-DFT) level, the luminescence decay is simulated by solving a 14 electronic states multimode problem including both vibronic and spin-orbit coupling (SOC) up to 15 vibrational modes. A careful analysis of the results provides the key features of the mechanism of the intersystem crossing (ISC) in this complex. The intermediate state, detected by means of fs - ps time-resolved spectroscopies, is assigned to the T state corresponding to the triplet intraligand ( IL) transition localized on the phen ligand. By switching off/on SOC and vibronic coupling in the model it is shown that efficient population transfer occurs from the optically active metal-to-ligand-charge-transfer1,3MLCT states to T and to the lowest long-lived phosphorescent MLCT (T ) state. The early ultrafast SOC-driven decay followed by a T /T equilibration controlled by vibronic coupling underlies the photoluminescent properties of [Re(CO) (phen)(im)] . The impact of the axial and N,N ligands on the photophysics of this class of Re(I) complexes is further rationalized on the basis of their calculated optical properties. The relative position of the IL and upper MLCT states with respect to the optically active singlet state is influenced by the N,N ligand and affects the relaxation dynamics.